2017
DOI: 10.14202/vetworld.2017.112-120
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers for resistance against infectious diseases of economic importance

Abstract: Huge livestock population of India is under threat by a large number of endemic infectious (bacterial, viral, and parasitic) diseases. These diseases are associated with high rates of morbidity and mortality, particularly in exotic and crossbred cattle. Beside morbidity and mortality, economic losses by these diseases occur through reduced fertility, production losses, etc. Some of the major infectious diseases which have great economic impact on Indian dairy industries are tuberculosis (TB), Johne’s disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 70 publications
1
17
0
5
Order By: Relevance
“…Strategies to counteract stress in humans and animals often rely on the early detection of stress-induced damage. Various indicators have been identified as potent markers of different biological processes, such as pathogenic or pharmacological responses, and are designated as biomarkers (Griffiths and Moller, 2002; Dadar et al, 2016; Abbas et al, 2017; Prajapati et al, 2017; Selleck et al, 2017; Ewert and Chang, 2018; Tampa et al, 2018). These include normal physiological biomarkers that are within the normal range in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to counteract stress in humans and animals often rely on the early detection of stress-induced damage. Various indicators have been identified as potent markers of different biological processes, such as pathogenic or pharmacological responses, and are designated as biomarkers (Griffiths and Moller, 2002; Dadar et al, 2016; Abbas et al, 2017; Prajapati et al, 2017; Selleck et al, 2017; Ewert and Chang, 2018; Tampa et al, 2018). These include normal physiological biomarkers that are within the normal range in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Its length ranges from 1-6 nucleotides (Van Oppen et al 2000) and can be classified as mono-, di-, tri-, tetra-, penta-and hexanucleotide repeats. With the minimum repeat length of 12 base-pairs they are tandemly repeated usually 5-20 times in the genome (Goodfellow 1992;Vaughan and Lloyd 2003;Ellegren 2004;Prajapati et al 2017). As a result of their quickness, simplicity, rich polymorphism and stability SSR markers are highly popular in genetic diversity analysis (Turkoglu et al 2013;Gürcan et al 2015;Batnini et al 2016), construction of fingerprints (Cantini et al 2001;Rojas et al 2008;Klabunde et al 2014;Turet-Sayar et al 2012;Ivanovych et al 2017), genetic purity test (Spann et al 2010), molecular map construction and gene mapping (Ogundiwin et al 2009;Olukolu et al 2009;Fan et al 2010;Pacheco et al 2014;Rowland et al 2014;Wang et al 2014;Eduardo et al 2015), utilization of heterosis, especially in the identification of species that are genetically related.…”
Section: Introductionmentioning
confidence: 99%
“…At the level of low divergence, quail seemed to be more close to chicken as compared to guinea fowl. Prajapati et al, (2017) mentioned that the breeding for genetic resistance is one of the promising ways to control the infectious diseases. Further, Malek and Lamont, (2003) indicated that Identification of candidate genes to improve the immune response may be useful for marker-assisted selection to enhance disease resistance, the polymorphism identified in iNOS CDS in present study, may be utilized for exploring the mechanism of higher disease resistance in guinea fowl, which may further be exploited to develop disease resistant chicken population.…”
Section: Phylogenetic Analysismentioning
confidence: 99%